Marketing Strategy Formulation for Affairs Store Yogyakarta - Anwar, Jihan Syifania; Wandebori, Harimukti (Journal of Business and Management, 2015)
Abstract - AFFAIRS store is one of fashion concept stores based in Yogyakarta and located at Jalan Ringroad Utara 20A, Pandega Satya, Kota Yogyakarta. The store is established since 2010 and it is the pioneer of concept store in Yogyakarta who sells fashion from various local brands. In order to expand their target market and sales, AFFAIRS needed to improve its current condition by seeing internal and external factor. Based on the interview and current facts in AFFAIRS store, it shows that the marketing mix strategies that have been done by AFFAIRS is still not working to the fullest and it will affect its brand equity dimensions of the store. AFFAIRS store needs to maximize their marketing mix strategies in order to expand their target market and increase their sales at the end. Therefore, this research examined the marketing strategy for concept store by identifying current marketing mix strategies in affecting brand equity dimensions and the current external and internal factors that will affect the condition of AFFAIRS store.Â Keywords - External and Internal Analysis, Marketing Mix, Brand Equity, Concept Store, Local Brand, Fashion.